Passive estimation of TCP round-trip times. - Jiang, Hao (Computer communication review.)
We propose and evaluate a passive measurement methodology that estimates the distribution of Round-Trip Times (RTTs) for the TCP connections that flow through a network link. Such an RTT distribution is important in buffer provisioning, configuration of active queue management, and detection of congestion unresponsive traffic. The proposed methodology is based on two techniques. The first technique is applicable to TCP caller-to-callee flows, and it is based on the 3-way handshake messages. The second technique is applicable to callee-to-caller flows, when the callee transfers a number of MSS segments to the caller, and it is based on the slow-start phase of TCP. The complete estimation algorithm reports an RTT for 55-85% of the TCP workload, in terms of bytes, in the traces that we examined. Verification experiments show that about 90% of the passive measurements are within 10% or 5ms, whichever is larger, of the RTT that ping would measure. Also, measurements on several NLANR traces show that the two estimation techniques agree within 25ms for 70-80% of the processed TCP connections. We also apply the estimation methodology on a number of NLANR traces and examine the variability of the measured RTT distributions in both short and long timescales.